Rapport management under examination in the context of medical consultations in Spain and Britain - Hernández López, María de la O (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2008)
This paper is framed within the areas of interactional pragmatics and social psychology of language, with a twofold purpose: on the one hand, applying Rapport Management (Spencer-Oatey, 2000, 2008) to the context of medical consultations in order to disentangle crucial similarities and differences between British and Spanish interactions; with the exception of Sydow Campbell’s (2005) study, Rapport Management has not been directly approached in this context. In this sense, it constitutes both a challenge in communication studies and a step forward in a well-known theory that still remains under-explored. On the other hand, Cordella’s (2004) voices in medical consultations will prove to be related to the way interlocutors manage rapport in each culture, and therefore, different voices may be relevant in different cultures. This will lead to variation in terms of the three bases of rapport (face, rights and obligations, and interactional goals). Finally, some remarks and limitations of Rapport Management will be discussed so as to give way to a more comprehensive and effective model of communication which may explain both cultural differences and situational variation.